Disclosure social um estudo comparativo entre empresas brasileiras e espanholas - Tessmann, Letícia Goulart dos Santos (Universidade do Vale do Rio dos Sinos, 2012)
The purpose of this study is to compare the social responsibility's disclosure within social reports of 30 Brazilian companies listed in the traditional market of BM&FBOVESPA and 30 Spanish companies listed in Madrid Stock Exchange that were published on 12/31/2010 and built the analyzed sample, considering categories and subcategories related to workforce, external public, environment, ethics and other social aspects. The investigative work is based in a descriptive, qualitative approach and a literature review. The analytic work was developed using content analysis technique with Sphinx 5.0 software, including descriptive and factorial analysis of the sentences related to its respective categories and subcategories. The results show a disclosure of 399 sentences total, those being 45% Brazilian and 55% Spanish companies, with a predominance of declarative type sentences. The subcategories with most number of sentences disclosed are related to training and professional development (workforce), education, health and sanitation (external public), environmental impacts and policies (environment). The ethical category still has a relatively small number of sentences in the reports. There is also a significant number of companies with no disclosure of social nature in their reports, which means that there is an important opportunity available for these companies to increase social nature disclosure.
Keywords: Ética empresarial; Responsabilidade social empresarial; Stakeholders; Business ethics; Corporate social responsibility; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis